Recent Advances of Graphitic Carbon Nitride-Based Structures and Applications in Catalyst, Sensing, Imaging, and LEDs - Wang, Aiwu; Wang, Chundong; Fu, Li; Wong-Ng, Winnie; Lan, Yucheng (Nano-Micro Letters, 2017)
The graphitic carbon nitride (g-C3N4) which is a two-dimensional conjugated polymer has drawn broad interdisciplinary attention as a low-cost, metal-free, and visible-light-responsive photocatalyst in the area of environmental remediation. The g-C3N4-based materials have excellent electronic band structures, electron-rich properties, basic surface functionalities, high physicochemical stabilities and are “earth-abundant.” This review summarizes the latest progress related to the design and construction of g-C3N4-based materials and their applications including catalysis, sensing, imaging, and white-light-emitting diodes. An outlook on possible further developments in g-C3N4-based research for emerging properties and applications is also included. Highlights: 1 The g-C3N4-based materials have excellent electronic band structures, electron-rich properties, basic surface functionalities, high physicochemical stabilities and are “earth-abundant.” 2 Recent progress of g-C3N4-based nanostructures in catalyst, sensing, imaging and LEDs have been discussed in details. 3 An outlook on possible further developments in g-C3N4-based research for emerging properties and applications is also included.